2002
DOI: 10.1046/j.1445-2197.2002.02405.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy following nodal surgery for melanoma: An analysis of late toxicity

Abstract: The regimen of radiation therapy used could form the basis for the treatment arm of a randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 22 publications
(39 reference statements)
4
30
0
Order By: Relevance
“…Melanoma patients were then stratified into 2 groups according to the anatomic region in which lymph node dissection was performed (ie, axillary and inguinofemoral). Six studies included both patients who had undergone axillary or inguinofemoral lymph node dissections, [16][17][18][19][20][21] ; the dissection groups from these studies are listed separately in Table 1. The pooled incidence of lower extremity lymphedema after inguinofemoral lymph node dissection was higher (18%) than for upper extremity lymphedema after axillary lymph node dissection (3%).…”
Section: Type Of Malignancymentioning
confidence: 99%
“…Melanoma patients were then stratified into 2 groups according to the anatomic region in which lymph node dissection was performed (ie, axillary and inguinofemoral). Six studies included both patients who had undergone axillary or inguinofemoral lymph node dissections, [16][17][18][19][20][21] ; the dissection groups from these studies are listed separately in Table 1. The pooled incidence of lower extremity lymphedema after inguinofemoral lymph node dissection was higher (18%) than for upper extremity lymphedema after axillary lymph node dissection (3%).…”
Section: Type Of Malignancymentioning
confidence: 99%
“…• Hypofractionated radiotherapy is well tolerated [29,30,35,48]. No grade-3 toxicity was reported by Bello et al [35] in 148 patients treated with 30 Gy in 5 fractions.…”
Section: Dose and Fractionationmentioning
confidence: 95%
“…Grade 4 toxicity resulting in complications such as skin ulceration, mucous membrane ulceration, and subcutaneous tissue necrosis was seen in 3% of patients treated to the groin. 81 In contrast, retrospective data from an MDACC series indicated that the 3-year actuarial rate of any grade 2 or 3 lymphedema following adjuvant irradiation of the inguinal nodes is 40% (27% for grade 2 alone). 84 The investigators also found that one-half of the patients who were scored as grade 2 lymphedema had evidence of lymphedema before radiation therapy.…”
Section: Toxicitymentioning
confidence: 96%
“…Another 2% of patients treated to the head and neck experienced severe induration and loss of subcutaneous tissue, or neck fibrosis. 81 However, surgery alone may cause long-term deficits. In one study of melanoma patients treated with cervical lymphadenectomy, 7% were found to have functional deficits and 6% of patients had long-term pain.…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation